2020
DOI: 10.1002/advs.202001019
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Regulation of Mesenchymal Genes Controls Fate Switches During Hematopoietic Differentiation of Human Pluripotent Stem Cells

Abstract: Epithelial-mesenchymal transition (EMT) or its reverse process mesenchymal-epithelial transition (MET) occurs in multiple physiological and pathological processes. However, whether an entire EMT-MET process exists and the potential function during human hematopoiesis remain largely elusive. Utilizing human pluripotent stem cell (hPSC)-based systems, it is discovered that while EMT occurs at the onset of human hematopoietic differentiation, MET is not detected subsequently during differentiation. Instead, a bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…1G), suggesting that a biphasic regulation of the cell cycle plays an important role in EHT. A previous report of the biphasic regulation of mesenchymal genes during EHT ( 27 ) was also confirmed in our study at the single-cell level. We demonstrated that the expression of mesenchymal genes was up-regulated before EHT and attenuated during EHT (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…1G), suggesting that a biphasic regulation of the cell cycle plays an important role in EHT. A previous report of the biphasic regulation of mesenchymal genes during EHT ( 27 ) was also confirmed in our study at the single-cell level. We demonstrated that the expression of mesenchymal genes was up-regulated before EHT and attenuated during EHT (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…1, F to H, and fig. S1F) ( 27 ). Last, the genes in cluster 4 were activated at the later stage of differentiation with predominant involved in EC-HC development (e.g., ESM1 and SPN ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, emerging evidence suggests that the plasticity of the epithelial–mesenchymal transition (EMT) phenotype of tumor cells had an important clinical significance for the progress of cancer and chemotherapy resistance. 40 , 41 In this study, we also observed genes negatively correlation with CYFIP2 were enriched on hallmark of EMT and angiogenesis. Taking together, we hypothesized that CYFIP2 might play a regulatory role in metabolic reprogramming and the EMT pathway in ccRCC.…”
Section: Discussionsupporting
confidence: 66%
“…The differentiation of hESCs to hematopoietic cells occurs in a sequential manner (Wang et al , 2018a; Wang et al , 2018b; Wang et al , 2020). This process involves exit from a pluripotent state and generation of lateral plate mesoderm cells (APLNR + ) at day 2.…”
Section: Resultsmentioning
confidence: 99%